Back Cover: [Am(C5Me4H)3]: An Organometallic Americium Complex (Angew. Chem. Int. Ed. 34/2019). Issue 34 (30th July 2019) - Goodwin, Conrad A. P.; Su, Jing; Albrecht‐Schmitt, Thomas E.; Blake, Anastasia V.; Batista, Enrique R.; Daly, Scott R.; Dehnen, Stefanie; Evans, William J.; Gaunt, Andrew J.; Kozimor, Stosh A.; Lichtenberger, Niels; Scott, Brian L.; et al.
Abstract : Organometallic americium synthetic chemistry has been dormant for decades. Now, E. R. Batista, W. J. Evans, A. J. Gaunt, S. A. Kozimor, P. Yang et al. report the crystallographically characterized complex [Am(C5 Me4 H)3 ], featuring the first quantitative measurement of Am−C molecular bonding interactions. In their Communication on page 11695 ff., spectroscopic comparison with ab initio calculations reveal a 5f 6 electronic configuration, and the 5f→5f/5f→6d transitions are accurately assigned. Graphic designed by Mr. Josh Smith, Chemistry Division, Los Alamos National Laboratory.